Designing an Omni-Experience to Save Retailing: Lessons from an Italian Book Retailer. Issue 3 (3rd May 2020) - Artusi, Federico; Bellini, Emilio; Dell'Era, Claudio; Verganti, Roberto
Abstract : Overview: Online-based retailers have made competing in the physical retail industry increasingly challenging. Building strong experiences to differentiate from the online-based players is key to survival. Brands can leverage different forms of engagement, such as sensorial or cognitive ones, to support their customer experience. "Read, Eat, Dream" (RED), a new concept by LaFeltrinelli, the major Italian bookseller, is an example of how to create an "omni-experience" by leveraging customers' lifestyles. This article outlines how LaFeltrinelli conceptualized and implemented the RED concept and presents four key design elements central to creating an omni-experience. By creating an omni-experience, retailers can transform from fulfillment centers to spaces where customers can engage, which in turn increases the length of their visit and occasions for purchase. An omni-experience also establishes the retail store as a reference point for some customers' specific activities.